The origami inspired optimization design to improve the crashworthiness of a multi-cell thin-walled structure for high speed train. (August 2019) - Wang, Shiming; Peng, Yong; Wang, Tiantian; Chen, Xuanzhen; Hou, Lin; Zhang, Honghao
Highlights: Parameterize the shape of the proposed origami structure. Propose an origami design to improve the initial peak force of thin-walled energy absorption structure for high speed train. Parametric studies are performed to evaluate the effects of design variables on collision responses. Response surface models are established to formulate the mathematical relationship between the crashworthiness responses and proposed structure dimensions. The optimized design is validated and the IPCF decreases by 29.36% comparing with the initial design without reducing the energy absorption. Abstract: The initial peak crushing force usually causes catastrophic harm to the passengers once vehicle collision accidents happen. In this study, an origami design is introduced and optimized to improve the initial peak crushing force ( IPCF ) of a thin-walled energy absorption structure. First, by analyzing the basic idea of origami structure, this paper decides twist angle (φ), height ( h) and thickness (t) as the control variables. Then, the crashing characteristics of the thin-walled structure are under study and the FE model is validated by an impact test. Further, parametric analysis on the relationships between design variables and target responses (energy absorption and IPCF ) is studied. It is found that the twist angle has a negative influence of IPCF and EA, while the t has a positive influence on the impact responses. Particularly, the increase of h cause the increase of IPCF but a decrease of EA. In further, to minimize the IPCF but do not affect the EA, optimization technology with NSGA-II algorithm is employed. The optimization results (i.e., φ  = 3.24°, h  = 30 mm, t  = 4 mm, IPCF  = 934.28 kN, EA  = 269.90 kJ) manifest that IPCF reduces by 29.36% without reducing the ability of energy absorption. For the point of train collision safety, the proposed origami inspired structure is introduced successfully and the optimal structure is of great advantages in improving the IPCF for the energy absorption structure.